Reading and preaching of the Psalms by Augustine: Lot and his family (Circe de clásicos y modernos, 2023)
The figure of Lot's wife appears frequently in the preaching of the great representatives of Latin spirituality of the 4th and 5th centuries, with the purpose of evoking the importance of the firmness of the vows for a Christian committed to his faith. This figure also has a long and varied exegetical tradition, which will be important to keep in mind to assess the contributions of our specific period of interest.
Keywords: Lot's wife; vows; salvation; salt; preaching